FAKTOR LINGKUNGAN YANG MEMPENGARUHI KEMATANGAN EMOSI REMAJA DALAM INTERAKSI SOSIAL KELAS XI DI SMA PGRI I PADANG - Sari, Gina Andria (Bimbingan dan Konseling, 2014)
This research was background by environment factor which is influence the maturity of teenager emotion. The purpose of this research to described : 1) family environment factor which is influencing teenager maturity emotion in social interaction at school, and 2) school environment which influence teenager maturity emotion in social interaction at school. This research used descriptive quantitative. Population of this research is 291 and sampling taken which is done is simple random sampling. This research take student as the sampling which as main respondent 69 students. The result stated that : 1) family factor which influence maturity of teenager emotion in many category of otoriter, allowance, comparing , and ambitious act which always forcing student, and democratic act. 2) school factor which influence maturity of teenager emotion in many category of positive thinking, empathy, and emotion controlling.